THE EFFECT OF TURMERIC ON ULCERATIVE COLITIS: A PERSPECTIVE: The Effect of Turmeric on Ulcerative Colitis - Araujo-Filho, Irami; Moraes da Cunha, Franciara Leticea; Meneses do Rêgo, Amália Cinthia (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2023)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease with limited treatment options and potential side effects. Curcumin, derived from Curcuma longa, has demonstrated anti-inflammatory and immunomodulatory properties, making it a potential therapeutic choice for UC. This review summarizes the literature on the impact of curcumin on UC management and its mechanisms of action. The included studies demonstrated that curcumin supplementation can lead to clinical remission, improved endoscopic findings, and reduced inflammatory markers in patients with UC. Curcumin's ability to target multiple pathways involved in the pathogenesis of UC makes it a promising adjunctive therapy. However, there are limitations due to the various study designs, curcumin dosages, and formulations. More well-designed clinical trials are needed to establish optimal dosing and evaluate long-term safety and efficacy. In conclusion, curcumin shows potential as a complementary therapy for UC due to its anti-inflammatory properties. Although more research is needed, current evidence suggests that curcumin supplementation may offer clinical benefits in managing UC. Future studies should standardize formulations, optimize dosages, and investigate long-term effects.